2020
DOI: 10.1002/glia.23843
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of dystonin in Schwann cells results in late‐onset neuropathy and sensory ataxia

Abstract: Dystonin (Dst) is a causative gene for Dystonia musculorum (dt) mice, which is an inherited disorder exhibiting dystonia‐like movement and ataxia with sensory degeneration. Dst is expressed in a variety of tissues, including the central nervous system and the peripheral nervous system (PNS), muscles, and skin. However, the Dst‐expressing cell type(s) for dt phenotypes have not been well characterized. To address the questions whether the disruption of Dst in Schwann cells induces movement disorders and how muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Conditional deletion of Plec from epidermal cells causes epidermal barrier defects and skin blistering ( Ackerl et al, 2007 ), both of which is more severe than that observed in dt mice carrying Dst-e mutations ( Guo et al, 1995 ; Yoshioka et al, 2020 ). Furthermore, we recently demonstrated that conditional deletion of Dst from Schwann cells in the peripheral nervous system leads to disorganization of the myelin sheath ( Horie et al, 2020 ), similar to that observed for Plec -deficient Schwann cells ( Walko et al, 2013 ). These studies suggest that Dst and plectin, which are plakin family proteins, have overlapping roles in different cell types.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Conditional deletion of Plec from epidermal cells causes epidermal barrier defects and skin blistering ( Ackerl et al, 2007 ), both of which is more severe than that observed in dt mice carrying Dst-e mutations ( Guo et al, 1995 ; Yoshioka et al, 2020 ). Furthermore, we recently demonstrated that conditional deletion of Dst from Schwann cells in the peripheral nervous system leads to disorganization of the myelin sheath ( Horie et al, 2020 ), similar to that observed for Plec -deficient Schwann cells ( Walko et al, 2013 ). These studies suggest that Dst and plectin, which are plakin family proteins, have overlapping roles in different cell types.…”
Section: Discussionmentioning
confidence: 62%
“…Some Dst-b E2610Ter/E2610Ter mice exhibited kyphosis (data not shown). We have reported that dt mice display impairment of motor coordination as assessed by the rotarod test and wire hang test ( Horie et al, 2020 ); however, WT and Dst-b E2610Ter/E2610Ter mice older than 1 year exhibited normal motor coordination ( Figure 2I ). These data also support the idea that deficiency of the Dst-a isoform, but not the Dst-b isoform, is causative of dt phenotypes, including sensory neuron degeneration, abnormal movements, and postnatal lethality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is probably due to differential recombination in Schwann cells. We have previously demonstrated the significance of Dst in Schwann cells for maintaining myelin sheaths in the PNS ( 43 ). Conditional Dst deletion in Schwann cells using a P0-Cre transgene resulted in late-onset neuropathy with prolongation of M response latency.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry (IHC) on paraffin sections was performed as previously described (Horie et al, 2020; Takebayashi et al, 2000). Paraffin sections were deparaffinized with xylene, rehydrated through a descending ethanol series, and immersed in distilled water.…”
Section: Methodsmentioning
confidence: 99%